Characterizing the S‐layer structure and anti‐S‐layer antibody recognition on intact Tannerella forsythia cells by scanning probe microscopy and small angle X‐ray scattering. Issue 11 (1st October 2013) - Oh, Yoo Jin; Sekot, Gerhard; Duman, Memed; Chtcheglova, Lilia; Messner, Paul; Peterlik, Herwig; Schäffer, Christina; Hinterdorfer, Peter
<x xml:space="preserve">Abstract</x> Tannerella forsythia is among the most potent triggers of periodontal diseases, and approaches to understand underlying mechanisms are currently intensively pursued. A 22‐nm‐thick, 2D crystalline surface (S‐) layer that completely covers Tannerella forsythia cells is crucially involved in the bacterium–host cross‐talk. The S‐layer is composed of two intercalating glycoproteins (TfsA‐GP, TfsB‐GP) that are aligned into a periodic lattice. To characterize this unique S‐layer structure at the nanometer scale directly on intact T. forsythia cells, three complementary methods, i.e., small‐angle X‐ray scattering (SAXS), atomic force microscopy (AFM), and single‐molecular force spectroscopy (SMFS), were applied. SAXS served as a difference method using signals from wild‐type and S‐layer‐deficient cells for data evaluation, revealing two possible models for the assembly of the glycoproteins. Direct high‐resolution imaging of the outer surface of T. forsythia wild‐type cells by AFM revealed a p4 structure with a lattice constant of 9.0 nm. In contrast, on mutant cells, no periodic lattice could be visualized. Additionally, SMFS was used to probe specific interaction forces between an anti‐TfsA antibody coupled to the AFM tip and the S‐layer as present on T. forsythia wild‐type and mutant cells, displaying TfsA‐GP alone. Unbinding forces between the antibody and wild‐type cells were greater than with mutant cells. This indicated that the TfsA‐GP is not so strongly attached to the mutant cell surface when the co‐assembling TfsB‐GP is missing. Altogether, the data gained from SAXS, AFM, and SMFS confirm the current model of the S‐layer architecture with two intercalating S‐layer glycoproteins and TfsA‐GP being mainly outwardly oriented. Copyright © 2013 John Wiley & Sons, Ltd.